Some reflections on the Epistemology of the natural factual sciences - Mesía Maraví, Rubén (2014)
This article begins by exposing the distinctive characteristics of the sciences. Continues to define the factual sciences, later to discuss the characteristics of the natural sciences. In a second part, discusses in some detail the methods of the natural sciences: the inductive and hypothetical-deductive method, the latter being the method most used explanation and research in science today. Finally, the article analyzes the falsificationism as criterion of demarcation scientific.